Risk preference, government regulation, and the sustainability of crop straw resource utilization—based on research data from Liaoning Province, China - Huang, Te; Guo, Yu; Zhou, Jing; Xiu, Liqun (Frontiers in Environmental Science, 2025)
IntroductionGlobal crop straw production has increased sharply, leading to serious challenges in straw burning and disposal. The unsustainable practice of open burning wastes valuable renewable resources and poses significant environmental threats, such as air pollution and soil degradation, that undermine global agricultural sustainability. Despite extensive efforts by the Chinese government to promote crop straw resource utilization (CSRU), low farmer participation and the reliance on a singular technological structure remain persistent issues.MethodsDrawing on prospect theory, this study integrates behavioral economics and policy analysis to examine how farmers’ risk preferences, including risk aversion, loss aversion, and nonlinear probability weighting, interact with heterogeneous government regulations, such as incentives, restrictions, and guidance, to shape CSRU behavior. Using micro-survey data from 440 rural households in Liaoning Province, China, we apply a logit model to quantify these relationships and analyze the moderating role of specific government policy measures.ResultsThe empirical results show that farmers generally exhibit strong risk aversion, which increases the average probability of CSRU adoption by 10.56%, meanwhile an excessive focus on low‐probability risks significantly promote adoption willingness. Furthermore, fiscal incentives such as direct subsidies effectively amplify the positive effect of risk aversion, increasing its marginal impact by 23.7%. In contrast, relying solely on regulatory measures tends to weaken this positive effect by increasing compliance costs, thereby reducing the adoption probability by 5.22%. Additional analysis reveals heterogeneity in responses based on income structures and business models: high‐level of part‐time farmers exhibit a much stronger response to government regulations, with their risk aversion effect being approximately 3.5 times that of low-level of part-time farmers.DiscussionBy synthesizing insights from behavioral and environmental economics, this study elucidates the mechanism through which economic risks are balanced in the CSRU adoption process and highlights the critical regulatory role of government policy tools. The findings provide empirical evidence and policy insights for optimizing resource management, formulating more cost-effective environmental policies, and promoting the green transformation of agriculture.